PERANCANGAN ULANG UNIT KERJA REKAM MEDIS DI RUMAH SAKIT UMUM RIZKI AMALIA MEDIKA LENDAH KULON PROGO - , VERONIKA TRI J ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:Rumah Sakit Umum Rizki Amalia Medika a is a new hospital was established in 2005. Currently processing medical records have not been implemented to the fullest. Still there is a delay in file processing, such as daily census and reporting. Though current medical record processing can improve the quality of a hospital. For it is necessary to design units of work appropriate medical records to create an orderly administration of the hospital. In supporting the implementation of the work unit maximum medical records, organizing, workspace layout medical records and job description has a very important role in the smooth processing of the file. Goals: draft organizational structure of the unit medical record, making the workspace layout design of medical records and drafted Job description medical records unit at Rumah Sakit Umum Rizki Amalia Medika. Methods: The design starts with analyzing the problem by making observations about the processing of medical records. Then identify needs done by interviewing the entire medical record officer. The next stage is to design a plan that has been prepared. The latter is a manifestation of that is done by presenting the results of the draft to the director of the hospital. Results: Based on the analysis of the problems that occur in the Rumah Sakit Umum Rizki Amalia Medika designer plan identifies needs that can be used to solve problems that are found there. Then the designer makes design work unit medical record in which includes organizational structure, layout workspace unit medical records, medical records and the job description.